The Institution of Gender-Based Asylum and Epistemic Injustice: A Structural Limit - Sertler, Ezgi (Feminist Philosophy Quarterly, 2018)
One of the recent attempts to explore epistemic dimensions of forced displacement focuses on the institution of gender-based asylum and hopes to detect forms of epistemic injustice within assessments of gender related asylum applications. Following this attempt, I aim in this paper to demonstrate how the institution of gender-based asylum is structured to produce epistemic injustice at least in the forms of testimonial injustice and contributory injustice. This structural limit becomes visible when we realize how the institution of asylum is formed to provide legitimacy to the institutional comfort the respective migration courts and boards enjoy. This institutional comfort afforded to migration boards and courts by the existing asylum regimes in the current order of nation-states leads to a systemic prioritization of state actors’ epistemic resources rather than that of applicants, which, in turn, results in epistemic injustice and impacts the determination of applicants’ refugee status.
Keywords: approches et analyses; capitalisme; confort institutionnel; cours; cycles supérieurs; discipline; fem9000; injustices testimoniales; injustices épistémiques; institutions; migration; philosophie; politiques migratoires; racisme; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences